(untitled) (Journal of Chemical Engineering, 2013)
To minimize the cost effective treatment process a treatment process has been setup at Dalas Fashion Ltd and Liz Fashion Ltd, Gazipur, Dhaka. The treatment process consisted of a combined process (anaerobic and bio-filtration process) to remove the pollution through biological process. The anaerobic process followed by Up-flow Anaerobic Sludge Blanket (UASB) process and Bio-filtration was maintained by polyurethane materials followed by down-flow process. The treatment processes are successfully operating without any chemical treatment process being thus more economic than the traditional chemical alternative. The raw textile wastewater is highly polluted with the characteristics of high alkaline in nature, pH=9-10, suspended biomass TSS= 1229-1500 mg/l, Chemical oxygen demand, CODt = 1448-2000 mg/l, and biological oxygen demand, BODt= 550-800 mg/l. Significant reductions were achieved to remove TSS (98%) through bio-filtration process. In addition in the final effluent the removal efficiency were found CODt (98%), BOD (94%) and color were removed significantly. Total cost taka 89.84 million per year for the chemical ETP process. On the contrary, for UASB ETP requires a total cost taka 17.84 million per year. DOI: http://dx.doi.org/10.3329/jce.v27i1.15855 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 32-36